Design of Decision Support System for New Employee Acceptance with SAW and WP Method in CV Karya Lestari Abadi - Felivia Regie Tanjaya; Andi Leo (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2019)
The selection process for new employees at CV. Karya Lestari Abadi is carried out manually, the application file for new candidates will be evaluated by comparing the contents of the file with specified criteria. File selection that meets the criteria is then followed by an interview process. The series of processes is followed by a series of written tests, including psychological tests, academic potential tests and so on. This study aims to build a New Employee Recruitment Decision Support System using the Simple Additive Weighting (SAW) and Weight Product (WP) methods. These two methods were chosen because they can determine the weight value for each attribute, then proceed with the ranking process that will choose the best alternative from several alternatives.While the system implementation uses the PHP and MySQL programming languages ​​as a database. With the decision support system can help the Recruitment in making decisions in the recruitment process in CV. Karya Lestari Abadi easier and faster.